Corporate Governance dan Kinerja Keuangan : Dampaknya Pada Nilai Perusahaan - Andry Priharta; Yud Buana; Diana Diana; Fitriasari Sintarini (Jurnal Akuntansi dan Governance, 2022)
Firm value reflects the market price of the stock that investors are able to pay. CGPI, ROA, NIM and LDR are factors thought to influence PBV. Panel data regression analysis with the common effect model is used to analyze the influence between variables with the object of research by BUMN Banks in Indonesia. There are four banks in the population, all of which are sampled, namely Bank Negara Indonesia (BBNI), Bank Rakyat Indonesia (BBRI), Bank Tabungan Negara (BBTN) and Bank Mandiri (BMRI). The research period is from 2011 to 2020. The results showed that CGPI, ROA and NIM have a positive and significant effect, while LDR has a negative and significant effect on PBV.